2020
DOI: 10.1371/journal.pone.0239193
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of workplace violence against doctors practising modern medicine and the subsequent impact on patient care, in India

Abstract: Introduction The incidents of violence against doctors, leading to grievous injury and even death, seem to be on an increasing trend in recent years. There is a paucity of studies on workplace violence against doctors and its effect, in India. The present study was conducted to assess workplace violence faced by doctors, its effect on the psycho-social wellbeing of the treating doctor and, subsequently, on patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…The research literature shows that such violence leads to issues such as death ( 8 ), heart and brain disease ( 9 ), anxiety, depression ( 10 ), and posttraumatic stress disorder (PTSD) ( 11 , 12 ). Workplace violence also translates to high costs for the organization where it takes place, both in the short and long term, and decreases quality of care provided to all patients ( 13 , 14 ). In China, workplace violence in hospitals causes a lot of to change their majors and decreases the integrity of the healthcare provider–patient relationship ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The research literature shows that such violence leads to issues such as death ( 8 ), heart and brain disease ( 9 ), anxiety, depression ( 10 ), and posttraumatic stress disorder (PTSD) ( 11 , 12 ). Workplace violence also translates to high costs for the organization where it takes place, both in the short and long term, and decreases quality of care provided to all patients ( 13 , 14 ). In China, workplace violence in hospitals causes a lot of to change their majors and decreases the integrity of the healthcare provider–patient relationship ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Out of the total doctors who responded, 477 had faced violence at workplace; the findings of which are published elsewhere. 6 In this paper, we present the findings about impact of media news on patient management by the doctors who had not faced WPV before participation in the study. The mean (SD) age of doctors who did not face workplace violence was 40.3 (11.7) years.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier study found a similar tendency among doctors who faced workplace violence. 6 This is a significant finding as such behavioral change among doctors, irrespective of their experience of facing workplace violence is likely to increase treatment costs significantly. Not only that, the critical and valuable time, which might be utilized in the management of moribund emergency cases, is lost in the process of referral.…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier study, we had reported that three out of four practicing doctors in India experienced workplace violence in the last 12 months of their practice. [ 3 ] An increased prevalence of aggression at the workplace has created a high-pressure work environment for doctors, and often they are at a risk of being judged negatively and face the consequences of disdain from either patients or relatives of patients. [ 4 ] Significant effect of this violence was also noted to be associated with the psychosocial health of doctors which further affected the management of patients.…”
Section: Introductionmentioning
confidence: 99%